The Implementation Of Discretionary Fixed Costs For Textile Waste Craftsman - Hidayah, Retnoningrum; Suryarini, Trisni; Suryandari, Dhini; Kayati, Ima Nur; Islamiatun, Monita Bayu (Indonesian Journal of Devotion and Empowerment, 2024)
Competition in the business world is an interesting thing to always observe. The rapid spread of micro, small, and medium enterprises (MSMEs) has led to high levels of competition. This service activity aims to provide an understanding regarding the calculation of discretionary fixed costs so that producers can calculate the desired profit level. The ability of MSME actors in this matter will be very beneficial for the development of their business. The target of this service activity is textile waste craftsmen who are in Menguneng Village, Pekalongan. Activities were carried out with the lecture method and practice calculations. Activities begin with initial coordination with partners to determine implementation time and equipment. Next, training was carried out in lectures and question and answer methods as well as calculation practice. Finally, monitoring and evaluation is carried out periodically. The results of the program show that the craftsmen understand the importance of calculating discretionary fixed costs for MSMEs. Furthermore, the craftsmen have been able to calculate the selling price of the product according to the profit target. Furthermore, it is hoped that there will be a positive synergy between the government and MSME craftsmen to increase product marketing.